Pengaruh variasi starter dan konsentrasi ekstrak buah melon (Cucumis melo L.) terhadap sifat fisikokimia yogurt: Effect of starter variation and concentration of melon fruit extract (Cucumis melo L.) on physicochemical properties of yogurt - Azara, Rima; Saidi, Ida Agustini; Amarulloh, Rochma (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2023)
Yogurt is a processed fermented milk product that utilizes lactic acid bacteria. Yogurt as a source of probiotics is beneficial for maintaining the body's immunity. This research aims to make melon yogurt drink as an effort to improve the taste of yogurt which tends to be sour so that it is not too sour by adding melon fruit extract. The study was conducted by RAK (Randomized Block Design) by analyzing the characteristics of melon yogurt produced with various amounts of melon extract added (5, 10, 15, 20%) and the amount of yogurt starter added (3 and 5%). The results of the analysis showed that there was an interaction between the concentration of the yogurt starter and the concentration of melon fruit extract on the total soluble solids of melon yogurt. Whereas there was no interaction between yogurt starter concentration and melon fruit extract concentration on pH, total acid, viscosity, and color profile of melon yogurt. Starter concentration had a very significant effect on lightness, had a significant effect on total solids, pH, viscosity, and had no significant effect on total acid, redness and yellowness of melon yogurt. Melon fruit extract had a very significant effect on total solids, viscosity, lightness, and had a significant effect on yellowness, and had no significant effect on pH, total acid, and redness of melon fruit yogurt.